Study The Effects of 5 Selenocyantouracil Compound on The liver and Kidney of Male Rats After Acetaminophen-Induced Liver Injury - Noori, Sahar Muayad; Neamah, Nadheerah Falih; Al-Jadaan, Shaker Abdalsalim (Iraqi Journal of Pharmaceutical Sciences, 2024)
Selenium compounds have long been assumed to protect organs against inflammation and cancer development by reducing oxidative stress. Drug-induced liver injury is a common side effect of many medications, with main symptoms ranging from an increase in asymptomatic liver enzymes to liver failure such as acetaminophen (AAP). The main objective of the present work is the protective effect of 5 selenocyantouracil (5SeU) against liver and kidney damage induced by AAP. Fifty male rats were divided into 4 groups consisting: Group A: rats were given only food and distal water (DW). Group B: rats were treated with acetaminophen (500mg/kg). Group C: rats were given acetaminophen in the preceding dose, and 5SeU (50 mg/kg). Group D: rats were treated with acetaminophen orally at the prior dose, and 5SeU (100mg/kg) orally once daily for 21 days. The results revealed significant differences of liver enzymes, urea and creatinine values at 5SeU treated groups in comparison with AAP group. Histopathological examinations confirm such results. As a conclusion, 5SeU compound has a protective activity against AAP-induced tissue damage.